GAMBARAN RESILIENSI PERAWAT RUMAH SAKIT UMUM DAERAH BALI MANDARA DI MASA PANDEMI COVID-19 - Swandewi, Made Adi; Suarningsih, Ni Kadek Ayu; Kamayani, Made Oka Ari (Coping: Community of Publishing in Nursing; Vol 11 No 4 (2023): Agustus 2023DO - 10.24843/coping.2023.v11.i04.p09, 2023)
Resilience is a person's ability to adapt well in the face of difficult and challenging experiences. Resilience can be seen both positively and negatively. The degree to which a person may be resilient varies greatly depending on their unique circumstances and challenges. The COVID-19 pandemic has caused nurses to experience situations of stress and mental problems. This study aimed to describe the resilience of nurses at the Bali Mandara Regional General Hospital during the COVID-19 pandemic. This research was a descriptive-analytic study with a cross-sectional design. It included a total of 78 respondents through a simple random sampling technique. The results showed that most respondents were female (70,5%) and married (75,6%). A total of 64,1% of respondents were registered nurses, have worked experience for more than 3 years (80,8%) and most of them worked in COVID-19 isolation room (25,5%). Only 6,4% of respondents were found to have a low resilience category. The majority of respondents who have moderate resilience were registered nurses (60%), married (78,3%), work experience > 3 years (81,7%), and placed inpatient room (23,3%). Meanwhile, respondents who have high category resilience mostly work in the COVID-19 isolation room (69,2%) and have work experience of > 3 years (69,2%). Characteristics of respondents are predicted to have a relationship with the level of resilience possessed by nurses in this study.